2001
DOI: 10.1046/j.1440-1762.2001.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality management and the Emergency Services Enhancement Program

Abstract: Since the introduction of the Emergency Services Enhancement Program (ESEP) in Victoria in 1995, improvements have been demonstrated in the indicators relating to Emergency waiting times, ambulance bypass rates and inpatient bed access block. This study focuses on staff perceptions of changes in these indicators, factors perceived to influence performance improvements and the extent to which ESEP is perceived to have contributed to overall patient care. A questionnaire was directed at four focus groups within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Multifaceted, multidisciplinary and hospital interventions are believed more likely to improve health outcomes than single‐faceted and single hospital interventions 13,14 . However, 89% of the evidence reported in Table 2 derives from single hospital interventions 19–23,25–26,29–44,46,49–63,65,67–71 and only 11% from multicentre interventions 27,45,47–48,64 …”
Section: Resultsmentioning
confidence: 99%
“…Multifaceted, multidisciplinary and hospital interventions are believed more likely to improve health outcomes than single‐faceted and single hospital interventions 13,14 . However, 89% of the evidence reported in Table 2 derives from single hospital interventions 19–23,25–26,29–44,46,49–63,65,67–71 and only 11% from multicentre interventions 27,45,47–48,64 …”
Section: Resultsmentioning
confidence: 99%
“…Cameron et al have suggested that the traditional model of hospital beds is not sustainable into the future 4 . These authors and others 15 have also indicated an association between access block and ambulance diversion. Our study is consistent with those findings.…”
Section: Discussionmentioning
confidence: 95%
“…Patients who were brought to EDs by any kind of ambulance had higher rates of access block 4 , 15 . This may be associated with complexity of illness, as patients in triage categories 2 and 3 had a higher rate of access block than others.…”
Section: Discussionmentioning
confidence: 99%
“…Cobelas et al concluded that when a hospital meets a patient's needs at a higher level than he/she expects, then this patient will not change the hospital ( Cobelas et al, 2001 ). Adeleke ( Adeleke & Aminu, 2012 ) introduced three factors of ‘the quality of services’, ‘customer satisfaction’ and ‘the perception of participation’ as three main factors of customer loyalty.…”
Section: Discussionmentioning
confidence: 99%